Endoscopy in Small Bowel Diseases - Goenka, Mahesh; Goenka, Usha; Rodge, Gajanan A. (IntechOpen, 2021)
This book examines endoscopy for small bowel diseases with special emphasis on inflammatory bowel disease (IBD), including a chapter on radiological imaging in IBD. The book reviews not only the history and art of small bowel endoscopy but also covers other aspects like endoscopic ultrasound assessment of the duodenal wall, intra-operative endoscopy, and management of small bowel perforations. We hope this book will help in the management of patients with small bowel diseases.